The use of nonlinear mono kinetics in modeling a mixing aeration tank with a biofilm on additional loading - Oleynik, Aleksandr; Kalugin, Yuriy; Airapetian, Tamara (Eastern-European Journal of Enterprise Technologies, 2017)
The paper presents a theoretical substantiation and methods of calculating biological wastewater treatment against organic pollutants (OPs) in aerotanks-mixers with a suspended (freely floating) biocenosis in the form of flakes of active sludge and a fixed biocenosis in the form of a biofilm on the surface of additional loading. A mathematical model is proposed in which the kinetics of the reactions of organic contamination extraction in aerotanks-mixers with suspended and fixed biocenoses are described by a nonlinear Mono equation. This model takes into account the provision of the oxidation process with a sufficient amount of oxygen and the peculiarities of the joint removal of organic pollutants by the biofilm that is formed on the surface of additional loading and the suspended biocenosis in the aerotank volume. Numerical methods were used to have determined the concentrations on the external and internal surfaces of the biofilm, which help estimate the value of the influxes of pollutants at the entrance and exist of the tank and thus assess the possible effect of cleaning. The numerical methods of purifying wastewater from organic pollutants in aerotanks-mixers, determined by numerical methods, show significant efficiency of the work of the purification structures due to the introduction of additional loading with a fixed biocenosis (biofilm). In this case, the possible technological and design schemes of the aerotank-mixer operation are considered, when the loading elements (nozzles, grids, etc.) can be located throughout the aerotank volume or more densely and compactly only in its specific areas